The Labour Market for Native and International PhD Students: Similarities, Differences, and the Role of (University) Employers - Massimiliano Tani (Institute of Labor Economics (IZA), 2020)
This paper studies the labour market outcomes of native and foreign PhD graduates staying as migrants in Australia, using data on career destinations over the period 1999-2015. Natives with an English-speaking background emerge as benefiting from positive employer discrimination, especially if graduating in Science, Technology, Engineering and Mathematics (STEM), for which they receive a premium that is unrelated to observed characteristics such as gender, age, and previous work experience. In contrast, foreign PhD graduates with a non-English speaking background experience worse labour market outcomes, especially if they work in the university sector. Acquiring education in the host country does not appear to eliminate uneven labour market outcomes between natives and foreigners.
Keywords: I26; J24; J31; J61; 330; PhD graduates; wage decomposition; discrimination; international students